(untitled) (مجلة إحالات, 2026)
Children’s literature is an educational medium that provides children with the opportunity to achieve self-confidence, freedom from the usual methods of thinking for discovery, and the interaction with modern digital media. As we are witnessing the challenges of globalization, e-culture has left a clear mark on the stage of life and penetrated sectors of society. It has also created a massive coup in which individual relations with the world have been touched by the concepts of the universe and the traditional frameworks of time. The whole world has become a complex network of interactions that transcend borders through rapid communication that acquires the child emotionally and mentally. so we tried to highlight the causes and manifestations of the fluctuation of the personality of the Arab’s child in the light of the current -culture progression. Also, it aimsatsuggesting solutions that help rebuilding a balanced personality and seek to promote children’s literature in both form and content.